Probability Judgment Error and Speculation in Laboratory Asset Market Bubbles - Ackert, Lucy F.; Charupat, Narat; Deaves, Richard; Kluger, Brian D. (Journal of Financial and Quantitative Analysis, 2009)
In 12 sessions conducted in a typical bubble-generating experimental environment, we design a pair of assets that can detect both irrationality and speculative behavior. The specific form of irrationality we investigate is the probability judgment error associated with low-probability, high-payoff outcomes. Independently, we test for speculation by comparing prices of identically paying assets in multiperiod versus single-period markets. We establish that aggregate irrationality measured in one dimension (probability judgment error) is associated with aggregate irrationality measured in another (bubble formation).